Poisoning deaths in Poland: Types and frequencies reported in Łódź, Kraków, Sosnowiec, Gdańsk, Wrocław and Poznań during 2009–2013 - Anna Krakowiak; Anna Piekarska-Wijatkowska; Katarzyna Kobza-Sindlewska; Anna Rogaczewska; Piotr Politański; Piotr Hydzik; Beata Szkolnicka; Tomasz Kłopotowski; Sebastian Picheta; Barbara Porębska; Andrzej Antończyk; Wojciech Waldman; et al. (International Journal of Occupational Medicine and Environmental Health, 2017)
Objectives: The aim of this study has been to assess the characteristics of acute poisoning deaths in Poland over a period of time 2009–2013. Material and Methods: The analysis was based on the data obtained from the patient records stored in toxicology departments in 6 cities – Łódź, Kraków, Sosnowiec, Gdańsk, Wrocław and Poznań. Toxicological analyses were routinely performed in blood and/or urine. Major toxic substances were classified to one of the following categories: pharmaceuticals, alcohol group poisonings (ethanol and other alcohols), gases, solvents, drugs of abuse, pesticides, metals, mushrooms, others. Cases were analyzed according to the following criteria: year, age and gender of analyzed patients, toxic substance category and type of poisoning. The recorded fatal poisonings were classified according to the International Classification of Diseases. Results: The record of 261 deaths were retrospectively reviewed. There were 187 males (71.64%) and 74 females (28.36%) and the male to female ratio was 2.52. Alcohol group poisonings were more frequently responsible for deaths in men compared to all poisonings, 91.1% vs. 71.6%, respectively (p < 0.05), and pharmaceutical agents were more frequently responsible for deaths in women, 47.4% vs. 28.4%, (p < 0.05). Methanol was the most common agent in the alcohol group poisonings, accounting for 43.75% (N = 49), followed by ethylene glycol, 39.29% (N = 44), and ethanol, 16.96% (N = 19). Conclusions: Epidemiological profile data from investigation of poisoning deaths in Poland may be very useful for the development of preventive programs. Int J Occup Med Environ Health 2017;30(6):897–908